Use of external cephalic version in Portuguese public hospitals. Issue 2 (15th February 2022) - Pinto, Luísa; Clode, Nuno; Ayres‐de‐Campos, Diogo
Abstract: Objective: To evaluate the use of external cephalic version (ECV) in Portuguese public hospitals with maternity services, as well as exploring the main motives for not offering the technique. Methods: A cross‐sectional observational study was conducted involving an online survey with 34 questions, accessed via an email addressed to all Heads of Department of Portuguese state‐owned hospitals with maternity services. In centers where the technique was performed, information was requested on success rates, contraindications for the procedure, and practical aspects related to its use. In centers where ECV was not offered, the underlying reasons for this were queried. Results: Answers were received from 41 out of the 43 state hospitals with maternity services (95.3%). Sixteen hospitals perform the technique (39%), with reported annual numbers ranging from 3 to 51, and success rates ranging from 25% to 85% (12 respondents). The main reasons for not offering the technique were lack of experience and lack of conditions to perform it safely. Most centers (87.8%) reported that they would welcome hands‐on training in ECV. Conclusion: ECV is used in a minority of Portuguese state‐owned hospitals. Efforts are needed to achieve a wider implementation of the technique, with a particular focus on simulation‐based training. Abstract : External cephalic version is used in a minority of Portuguese public hospitals. Efforts are needed in order to achieve a wider dissemination of the technique.